Pengaruh Reward terhadap Peningkatan Prestasi Belajar Siswa di SDN Banjardowo 1 Jombang - Eny Fatimatuszuhro Pahlawati; Iis Novita Ratna Sari (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study aims to determine whether there is a significant influence between Reward on improving student learning achievement at SDN 1 Banjardowo Jombang.  The type of research used in this study is quantitative research with the study population were all students at SDN 1 Banjardowo Jombang. Because the population is considered a lot, the authors use a sample of class V students as many as 35 students studied. To collect data in this study, the authors used questionnaires, and documentation. The questionnaire distributed by the writer is a closed questionnaire, consisting of four alternative answers, namely SS, S, TS, STS. To analyze the data the author uses product moment correlation analysis.  Based on the results of data analysis it turns out that Ha can be accepted at a correlation value of 5% because this is evidenced from the results of product moment correlation states table r0,3957> 0.3388 so that it can be concluded that there is a significant effect between reward and learning achievement of students at Banjardowo Jombang 1 State Elementary School.